RELATIONSHIP BETWEEN CONTRACEPTIVE USE AND OCCUPATIONAL STATUS WITH UNWANTED PREGNACNY RISK AMONG COUPLES OF CHILDBEARING AGE - Novela Sanderina Rumaropen; Lutfi Agus Salim; Salut Muhidin (Universitas Airlangga, 2020)
Unwanted pregnancy is a world problem. In 2008, there were 208 million pregnancies in the world, and 41% of them were unwanted pregnancy. Cross-national reproductive health studies have indicated that the unwanted pregnancy rates remain substantially high in many developing regions, including in Indonesia (Bearak et al. 2018). Unwanted pregnancies in Indonesia increased from 13.6% in 2012 to 16% in 2015. The high rates of unwanted pregnancies are often linked to the gaps in family planning services such as the effective use of contraceptive methods which is also influenced by family socioeconomic backgrounds such as their occupational status. Using the case study at health clinics of PKBI in East Java, this paper attempts to explore the association or relationship between the risk of unwanted pregnancy among couples of childbearing age (CCA) with their use of contraceptive methods and occupational status. A quantitative method of a case-control research design was applied by using a random sampling technique. The study was 50 women couples of childbearing age (15–45 years), who had unwanted and wanted pregnancies. Simple correlation analysis shows that the association are relatively significant between the occurrence of an unwanted pregnancy with the long-term contraceptive use (p-value = 0.008), and with the employed in occupational status (p-value = 0.027). However, there is no correlation between the unwanted pregnancy occurrence with the short-term contraceptives use (p-value = 0.118). The study concludes that the use of short-term contraceptive methods and the employed status can still affect the risk of unwanted pregnancies, while the effective use of long-term contraceptive method has a vital role in preventing unwanted pregnancies.